Strategies and challenges in maintaining the mental health of nursing professionals in the context of the Covid-19 pandemic (Research, Society and Development, 2021)
To analyze published scientific evidence on strategies and challenges in maintaining the mental health of nursing professionals in the context of the Covid-19 pandemic. This study is a literature review of the integrative literature review method, carried out in the months between January and May 2021. The search was carried out through the Virtual Health Library Platform - VHL, using databases (LILACS) , (BDENF), through (SCIELO). Adhering through the descriptors/key words: “Nursing”, “Mental Health”, “Covid-19”, combined with the Boolean operator “AND”. The professional is exposed and can lead to psychological distress, high stress, anxiety, depression. These comorbidities, when present, can negatively impact job satisfaction, resulting in damage to care, quality of care and patient safety. It is currently common to identify symptoms of anxiety and depression and the great impact that these manifestations have on the well-being and daily activities of health workers. In nursing, there is a large index of these psychic manifestations among professionals. It is noteworthy that all these stressors related to nursing work tend to be exacerbated in the face of a calamity scenario such as the one that has been installed in recent times, as the world is currently going through a period of turmoil resulting from the pandemic caused by the new coronavirus. In this context, it is necessary to implement psychological support interventions for this group, considering that health professionals are at significantly high risk and have psychopathologies such as: anxiety, depression, stress, insomnia, fear, PTSD, syndrome of Burnout.